Emerging Research Trends in Experiential Learning in Higher Education: A Scopus Database Bibliometric Analysis - Mertayasa, I Komang; Pandang, Abdullah; Arismunandar, Arismunandar; Ansar, Ansar (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to map global research developments on experiential learning (EL) in higher education by employing a bibliometric approach. Experiential learning has gained increasing attention as a transformative pedagogy that connects theoretical understanding with real-world application. Research data were collected from the Scopus database for the years 2023–2025 and analyzed using VOSviewer and Biblioshiny to examine publication trends, citation patterns, author productivity, and thematic clusters. The findings reveal a sharp and consistent increase in EL-related publications worldwide, with the United States, Canada, and the United Kingdom emerging as the most productive countries, while Southeast Asia—particularly Indonesia—shows relatively limited contributions. The analysis also identifies several emerging thematic clusters, including the integration of EL with immersive technologies such as artificial intelligence, virtual reality, and the metaverse, as well as applications in service learning, entrepreneurship education, and authentic assessment. The novelty of this study lies in its focused examination of the 2023–2025 publication period, capturing the latest global trends shaped by digital transformation and sustainability agendas. Practically, the results highlight the need for stronger institutional and policy support to systematically embed EL within higher education curricula. Overall, this study contributes to strengthening evidence-based, student-centered learning and informs future research opportunities in experiential education.